Histone post-translational modifications in Silene latifolia X and Y chromosomes suggest a mammal-like dosage compensation system - Rodríguez Lorenzo, José Luis; Hubinský, Marcel; Vyskot, Boris; Hobza, Roman (Plant science, 2020)
Silene latifolia is a model organism to study evolutionary young heteromorphic sex chromosome evolution in plants. Previous research indicates a Y-allele gene degeneration and a dosage compensation system already operating. Here, we propose an epigenetic approach based on analysis of several histone post-translational modifications (PTMs) to find the first epigenetic hints of the X:Y sex chromosome system regulation in S. latifolia. Through chromatin immunoprecipitation we interrogated six genes from X and Y alleles. Several histone PTMS linked to DNA methylation and transcriptional repression (H3K27me3, H3K23me, H3K9me2 and H3K9me3) and to transcriptional activation (H3K4me3 and H4K5, 8, 12, 16ac) were used. DNA enrichment (Immunoprecipitated DNA/input DNA) was analyzed and showed three main results: (i) promoters of the Y allele are associated with heterochromatin marks, (ii) promoters of the X allele in males are associated with activation of transcription marks and finally, (iii) promoters of X alleles in females are associated with active and repressive marks. Our finding indicates a transcription activation of X allele and transcription repression of Y allele in males. In females we found a possible differential regulation (up X1, down X2) of each female X allele. These results agree with the mammal-like epigenetic dosage compensation regulation.
Keywords: histony; Histone PTMs; Silene latifolia; Sex chromosome evolution; Histones; Epigenetics; Dosage compensation; Silene; Protein Processing, Post-Translational; Dosage Compensation, Genetic; Plant Proteins; kompenzace dávky (genetika); chromozomy rostlin; posttranslační úpravy proteinů; rostlinné proteiny; Chromosomes, Plant